64Cu-Labeled multifunctional dendrimers for targeted tumor PET imaging. Issue 13 (16th March 2018) - Ma, Wenhui; Fu, Fanfan; Zhu, Jingyi; Huang, Rui; Zhu, Yizhou; Liu, Zhenwei; Wang, Jing; Conti, Peter S.; Shi, Xiangyang; Chen, Kai
Abstract : Multifunctional folic acid-modified G5 PAMAM dendrimers can be radiolabeled with 64 Cu for PET imaging of folate receptor-expressing tumors. Abstract : We report the use of multifunctional folic acid (FA)-modified dendrimers as a platform to radiolabel with 64 Cu for PET imaging of folate receptor (FR)-expressing tumors. In this study, amine-terminated generation 5 (G5) poly(amidoamine) dendrimers were sequentially modified with fluorescein isothiocyanate (FI), FA, and 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA), followed by acetylation of the remaining dendrimer terminal amines. The as-formed multifunctional DOTA-FA-FI-G5·NHAc dendrimers were then radiolabeled with 64 Cu via the DOTA chelation. We show that the FA modification renders the dendrimers with targeting specificity to cancer cells overexpressing FR in vitro . Importantly, the radiolabeled 64 Cu-DOTA-FA-FI-G5·NHAc dendrimers can be used as a nanoprobe for specific targeting of FR-overexpressing cancer cells in vitro and targeted microPET imaging of the FR-expressing xenografted tumor model in vivo . The developed 64 Cu-labeled multifunctional dendrimeric nanoprobe may hold great promise to be used for targeted PET imaging of different types of FR-expressing cancer.